FROM CIVITAS SOLIS TO THE EXISTENTIAL CITY: PHILOSOPHICAL FOUNDATIONS OF BIONIC ARCHITECTURE - Kiuntsli Р.; Stepaniuk А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
This article examines bionic architecture as a profound philosophical reflection on spatial design in the age of urban expansion, environmental challenges, and technological acceleration. Building upon the utopian visions of the “City of the Sun,” the authors trace the intellectual shift towards the “existential city” – an architectural paradigm where space is not merely functional but deeply resonant with the human inner world. Bionics is presented not only as an aesthetic or technological approach but as a holistic worldview that integrates cultural memory, ecological ethics, and archetypal symbolism. The paper focuses on the capacity of bionic environments to adapt, breathe, and alleviate psychological stress. It analyzes both historical (A. Gaudí, R. Steiner, I. Makovecz) and contemporary architectural projects (The Eden Project, Eastgate Centre, Vincent Callebaut’s concepts) to reveal the philosophical power of bionics. The authors argue that the essence of bionic design lies not in mimicking nature, but in cultivating an ethical dialogue between humans and their environment. Special attention is given to bionics as a language of architectural thinking, capable of expressing spiritual meanings within the built environment. In this regard, bionic design serves as a mediator between cultural heritage, technological innovation, and contemporary human needs. The article emphasizes how organic forms reduce anxiety, foster environmental awareness, and help reimagine space as a supportive and meaningful setting. Ultimately, bionic architecture is shown to be more than a tool for sustainability or energy efficiency – it becomes a spatial philosophy that bridges nature, technology, and human consciousness. This article frames bionics as an architectural language of empathy, meaning, and ecological responsibility, relevant for the spiritual and material needs of the 21st century.